2007
DOI: 10.1538/expanim.56.149
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of IRS-2 Deficient Mice Produced by Reproductive Technology are Stable

Abstract: We studied the impact of "IVF -ET" on the glucose tolerance test (GTT), insulin tolerance test (ITT) and adiponectin to investigate differences in the phenotypes of B6J-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Data for the B6J-Irs2 -/-mouse are presented in this paper. The descriptions and data in the following sections are cited and abstracted from previous publications [2,[7][8][9][10].…”
Section: Irs2mentioning
confidence: 99%
“…Data for the B6J-Irs2 -/-mouse are presented in this paper. The descriptions and data in the following sections are cited and abstracted from previous publications [2,[7][8][9][10].…”
Section: Irs2mentioning
confidence: 99%
“…The noise levels were measured using a digital noise meter, SM-325 (AS ONE Corporation). All mice were provided with a radiation sterilized (50 kGy) feed for laboratory animals (CL-2, CLEA, Tokyo, Japan) and autoclave-sterilized (124℃, 15 …”
Section: Animalsmentioning
confidence: 99%
“…In research on intestinal flora and probiotics, animal experiments using germfree and gnotobiotic animals reared in vinyl isolators are essential [3]. Because insulin secretion as the pivotal index in diabetes research tends to vary in accordance with circadian rhythm [11,19], insulin secretion and sensitivity are usually evaluated by the glucose tolerance test (GTT) and the insulin tolerance test (ITT) [15,16,41]. However, sample correction for mice reared in vinyl isolators was performed by sacrifice under anesthesia, and in the insulin and glucose evaluations, factors of circadian rhythm cannot be eliminated and it is not possible to determine changes in the same individual mice.…”
Section: Introductionmentioning
confidence: 99%
“…1B), because the reproduction indexes of IVF-ET showed that the expansion of Irs2 -/-mice using IVF-ET only was impossible. Hashimoto et al reported that the phenotypes of Irs2 -/-mice were not affected by the reproduction method using IVF-ET [2]. In addition, use of vitrification [8] in IVF-ET might produce better results (Fig.…”
mentioning
confidence: 99%